Integration of Health Education and Cultural Value of Bimanesse Called “Maja Labo Dahu” toward the Intention to Stop Smoking of Smoker Student at Bima District-Indonesia (Medico Legal Update, 2021)
Socio-cultural elements may affect someone to follow or leave a behavior. Cultural values in the BimaDistrict-West Nusa Tenggara Province community that are in line with health behavior are the culturalvalues called “Maja Labo Dahu/MLD”, “Maja” means self-aware and “dahu” means carefulness. This studyaims to determine the effect of integrating the cultural value of “MLD” and health education toward theintention of high school student to stop smoking in Bima district . This study is a quasy experiment withpre-post-test with control group design with purposiv sampling on 60 students of 5 Senior High School inBima district. Self report was used to analyze the intention to stop smoking. Data analysis was examined byusing Pairred T-Test. The results showed 86.7% had strong intention to stop smoking and 13.3% had weakintention. The mean standard pre-post deviation in the treatment group was 4,633 ± 8,046 with a p-value